Improving Investment Understanding For Millennial Generation Through Digital Teaching Media Innovation - Wijaya, Bagus Kusuma; Radhitya, Made Leo; Suandana, Ni Putu Widantari (Jurnal Scientia, 2024)
This research explores the low financial literacy among millennials despite their dominance in the use of information technology. Various surveys show that most millennials cannot answer basic questions about finance and investment correctly, indicating an urgent need to improve financial and investment literacy. This lack of understanding of investment instruments and financial strategies negatively impacts their financial stability. Initial questionnaire results from 30 students showed that 70% felt unfamiliar with investments, while 30% felt familiar. In addition, students were most familiar with stocks (40%), followed by mutual funds (30%), cryptocurrencies (15%), and bonds (10%). The study also found that investment literacy and education activities can increase millennials' understanding and motivation to invest. Technology plays an important role in financial education, with well-designed digital learning media, such as e-books and other digital tools, significantly improving learning outcomes. Recommendations from this research include the provision of interactive and fun teaching materials that are easily accessible through digital media, covering the introduction of basic investment concepts, long-term returns, practical guidance on starting an investment, and risk management. This research emphasizes the importance of greater financial education and literacy efforts to empower millennials to manage their finances more effectively and wisely.